2011
DOI: 10.1128/aem.01289-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors and Influence of Rumen and Hindgut Biogeography on Bacterial Communities in Steers

Abstract: Feces from cattle production are considered important sources of bacterial contamination of food and the environment. Little is known about the combined effects of arctic temperatures and fodder tannins on rumen and hindgut bacterial populations. Individual rumen liquor and rectal fecal samples from donor steers fed either alfalfa silage or sainfoin (Onobrychis viciifolia Scop.) silage and water ad libitum were collected weekly on the first three sampling days and fortnightly afterwards. The daily ambient temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 44 publications
7
42
0
2
Order By: Relevance
“…Depending on the basal diet composition, this effect may be clearly advantageous for the animal, increasing the flow of non-degraded protein to the intestine. Romero-Pérez et al (2011) reported similar findings in an in vitro study conducted with rumen inoculum from cows fed alfalfa or sainfoin silages.…”
Section: Ruminal Biohydrogenationsupporting
confidence: 67%
See 1 more Smart Citation
“…Depending on the basal diet composition, this effect may be clearly advantageous for the animal, increasing the flow of non-degraded protein to the intestine. Romero-Pérez et al (2011) reported similar findings in an in vitro study conducted with rumen inoculum from cows fed alfalfa or sainfoin silages.…”
Section: Ruminal Biohydrogenationsupporting
confidence: 67%
“…In contrast to the consistent action of tannins on ruminal ammonia concentration, reports on the response of VFA to these secondary compounds are highly variable, with reductions, no effects and even increases in their production (e.g., Frutos et al, 2004a;Tiemann et al, 2008;Romero-Pérez et al, 2011). This discrepancy is even stronger when referred to individual VFA.…”
Section: Ruminal Biohydrogenationmentioning
confidence: 56%
“…Several clone libraries of rumen samples reported significant numbers of bacteria belonging to the phylum Verrucomicrobia (Romero-Perez et al, 2011;Godoy-Vitorino et al, 2012). Although their role in the rumen is not well understood, some members of the Verrucomicrobia have been found to oxidise CH 4 as the sole source of carbon and energy in non-rumen environments (Hou et al, 2008).…”
Section: Methylotrophsmentioning
confidence: 99%
“…Previous research has demonstrated that many factors influence the composition of rumen microbiota, affecting the population of certain bacterial groups (18,22,23,43). Microbial diversity and activities have also been influenced by modifications to the diet (11, 51).…”
mentioning
confidence: 99%